2008
DOI: 10.1021/om7009792
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of Borate Ester Coordinated Organobismuth Compounds

Abstract: A new class of hypervalent organobismuth compounds functionalized with coordinating pinacolborate esters of the nature ArBiCl 2 (2), Ar 3 Bi (3), ArPh 2 Bi (4), Ar 3 BiCl 2 (5), and ArPh 2 BiCl 2 (6), where Ar ) 3-fluoro-2-pinacolatoboronphenyl, have been prepared and structurally characterized. The Bi • • • O distance is between 2.58 and 3.47 Å in the solid state for all compounds, and reasonable bonding interactions are presumed to exist in compounds 2-4 and 6, where Bi • • • O < 3.0 Å. When ArPh 2 BiCl 2 ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…compounds IX and X). 95 Similar interactions within ortho-substituted triarylbismuthines were also observed by Caires 61 in 2008 and by Silvestru in 2010. 159 Hypervalent interactions have also been identified in pentavalent organobismuth compounds (Scheme 6 B).…”
Section: Hypervalency In Organobismuthinessupporting
confidence: 68%
See 2 more Smart Citations
“…compounds IX and X). 95 Similar interactions within ortho-substituted triarylbismuthines were also observed by Caires 61 in 2008 and by Silvestru in 2010. 159 Hypervalent interactions have also been identified in pentavalent organobismuth compounds (Scheme 6 B).…”
Section: Hypervalency In Organobismuthinessupporting
confidence: 68%
“…The introduction of more reactive functional groups on triarylbismuthines was accomplished using Grignard reagents prepared using Knochel's conditions (Step 14a). 60 Triarylbismuthines bearing imines, 56 nitriles, 51,56 esters 51,56 or borate esters 61 have been prepared using this approach.…”
Section: Synthesis Of Functionalized Triarylbismuthinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Caires et al [ 55 ] reported the first example of organobismuth compounds which contained organic boron groups. These organobismuth complexes were synthesized with a borate ester moiety because of its relative rarity as an oxygen donor in coordination compounds.…”
Section: Synthesis and Property Characterization Of Various Organomentioning
confidence: 99%
“…Iodinated arylboronic acids are attractive synthetic intermediates as they possess two sites, which can be employed in coupling reactions. Thus, pinacol esters of simple iodophenylboronic acids were used as precursors of magnesiumeboron bimetallics followed by the treatment with electrophiles to give functionalized arylboronic esters [1,2]. Recently, 2-iodophenylboronic acid was found to be an effective catalyst for the direct formation of amides from carboxylic acids and amines [3].…”
Section: Introductionmentioning
confidence: 99%